Seeing the Whole Elephant: a scoping review of behavioral treatments for pediatric insomnia. (April 2021) - Meltzer, Lisa J.; Wainer, Allison; Engstrom, Erin; Pepa, Lauren; Mindell, Jodi A.
Summary: Pediatric insomnia is common, impacting up to a third of typically-developing, healthy children, and over 80% of children with neurodevelopmental disorders or chronic medical conditions. Previous reviews of behavioral interventions for pediatric insomnia have had a limited focus on a single age group, a specific population, and/or only randomized controlled trials. Furthermore, few reviews have considered non-sleep outcomes of both children and their parents. This scoping review provides a broader context, including studies regardless of research design or population, along with sleep and non-sleep study outcomes. Clear gaps in the literature were identified, highlighting the need for additional research in different populations, including school-age children and adolescents, racial/ethnic groups around the world, as well as youth with medical or psychiatric disorders. In addition, more research is needed on different features of treatment, including the delivery mode, involvement of all family members, non-sleep outcomes, and long-term follow-up.